The Q - Tintera, Amy ([The Q], 2022)
When the president's son, Lennon, is kidnapped and pushed out of an airplane over the Q, a vast quarantine zone, Maisie gives him a seventy-two hour vaccine and together the two teenagers attempt to fight their way through the Q in order to survive.